2011
DOI: 10.4236/ojst.2011.13015
|View full text |Cite
|
Sign up to set email alerts
|

Non-odontogenic toothache revisited

Abstract: Although pain of dental origin is the most common orofacial pain, other non-odontogenic pains can af-fect the orofacial region and occasionally mimic den-tal pain. These non-odontogenic pains may pose a diagnostic dilemma for the dental practitioner who routinely diagnoses and treats dental pain. Knowledge of the various non-odontogenic pains will ultimately prevent misdiagnosis and the delivery of incorrect and sometimes irreversible and invasive procedures to patients. The purpose of this article is to revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
2
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 87 publications
2
21
2
2
Order By: Relevance
“…Non odontogenic toothache, as its name suggests, is a painful condition that occurs in the absence of any clinically evident cause in the teeth or periodontal tissues . Generally, 88% of patients with toothache‐like pain visit a dental office; 3% of these patients have nonodontogenic toothache, and 9% have a mixed condition of odontogenic and nonodontogenic toothache.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Non odontogenic toothache, as its name suggests, is a painful condition that occurs in the absence of any clinically evident cause in the teeth or periodontal tissues . Generally, 88% of patients with toothache‐like pain visit a dental office; 3% of these patients have nonodontogenic toothache, and 9% have a mixed condition of odontogenic and nonodontogenic toothache.…”
Section: Introductionmentioning
confidence: 99%
“…We concluded that unnecessary dental treatment should be avoided. KEYWORDS: toothache, myofascial pain syndromes, neuralgia, myofascial pain syndromes, cerebrovascular disorders, cardiovascular diseases Accepted for publication 13 June 2014 Background Non odontogenic toothache, as its name suggests, is a painful condition that occurs in the absence of any clinically evident cause in the teeth or periodontal tissues (1)(2)(3)(4). Generally, 88% of patients with toothache-like pain visit a dental office; 3% of these patients have nonodontogenic toothache, and 9% have a mixed condition of odontogenic and nonodontogenic toothache.…”
mentioning
confidence: 99%
“…Additionally, localized muscle tension, especially in the masseter, is commonly misconstrued as tooth pain. The current recommendations for treating pain of this type include muscle stretching and massage, much as Turi recommends [86]. …”
Section: Discussionmentioning
confidence: 99%
“…Às vezes é apenas irritante, mas em outras é penosa a ponto do paciente perder a consciência quando seu sistema não pode suportar a duração da experiência. De todos os sintomas que o cirurgião-dentista enfrenta, a dor é a mais pungente e livrar o paciente da dor é talvez o aspecto mais gratificante da prática [1][2][3] . Normalmente, a experiência da dor é iniciada em uma base fisiológica via sistema periférico.…”
Section: Introductionunclassified
“…A base neuroanatômica para a capacidade de localizar especificamente a dor intensa é ainda mal compreendida. Às vezes, o profissional pode encontrar sintomatologia dolorosa referida aos dentes e maxilares, porém de natureza não odontogênicas [1][2][3] . Apesar da maior compreensão acerca da dor orofacial nos últimos anos, o diagnóstico preciso da dor ainda é um desafio na odontologia contemporânea.…”
Section: Introductionunclassified